2015
DOI: 10.5194/hess-19-2491-2015
|View full text |Cite
|
Sign up to set email alerts
|

Using high-frequency water quality data to assess sampling strategies for the EU Water Framework Directive

Abstract: Abstract. The EU Water Framework Directive (WFD) requires that the ecological and chemical status of water bodies in Europe should be assessed, and action taken where possible to ensure that at least "good" quality is attained in each case by 2015. This paper is concerned with the accuracy and precision with which chemical status in rivers can be measured given certain sampling strategies, and how this can be improved. High-frequency (hourly) chemical data from four rivers in southern England were subsampled t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 17 publications
(35 reference statements)
2
72
0
Order By: Relevance
“…These were established using a Monte Carlo approach whereby the SSC record was sampled n times; where n is the a prioiri determined frequency of measurements over the entire monitoring period. For each measurement frequency the record was resampled 1000 times to produce an ensemble of measurements from which population statistics could be obtained (Skeffington et al, 2015). Following each sampling run, the number of samples was monotonically increased by one, with sample frequencies ranging from one sample per year, through to one every 15-min.…”
Section: Synthetic Concentration Recordmentioning
confidence: 99%
See 1 more Smart Citation
“…These were established using a Monte Carlo approach whereby the SSC record was sampled n times; where n is the a prioiri determined frequency of measurements over the entire monitoring period. For each measurement frequency the record was resampled 1000 times to produce an ensemble of measurements from which population statistics could be obtained (Skeffington et al, 2015). Following each sampling run, the number of samples was monotonically increased by one, with sample frequencies ranging from one sample per year, through to one every 15-min.…”
Section: Synthetic Concentration Recordmentioning
confidence: 99%
“…Grove et al, 2015;Johnes, 2007;Skeffington et al, 2015). This has implications not only for the characterisation of background levels of suspended sediment, but also particulate borne contaminants.…”
Section: Impact Of Sampling Frequency On Apparent Fine Sediment Exposurementioning
confidence: 99%
“…There is, therefore, increasing interest in the use of in-stream high resolution water quality monitoring to assemble higher resolution catchment-scale datasets (e.g. Bowes et al, 2015;Halliday et al, 2012;Jordan et al, 2012;Mellander et al, 2012;Mellander et al, 2014;Outram et al, 2014;Skeffington et al, 2015;Wade et al, 2012), which can be used to understand key catchment processes in terms of hydrology, diffuse pollution transfer and trophic impacts and how these may alter under a changing climate.…”
Section: Introductionmentioning
confidence: 99%
“…Carstensen (2007) concluded that the required monitoring efforts to ensure a precise quality assessment are substantially higher than envisaged in the WFD and, for phytoplankton and nutrients, may be as high as 500 observations to characterise a water body. However, a trade-off exists between the improved precision obtained by sampling more frequently and the economics of monitoring (Skeffington et al, 2015).…”
Section: Introductionmentioning
confidence: 99%